Redescription and new record of Odontoscirus nipponicus Shiba, 1985 (Bdellidae: Odontoscirinae) from China with a description of its ontogeny - Wu, You-Fang; Jin, Dao-Chao; Yi, Tian-Ci; Guo, Jian-Jun (Zootaxa, 2022)
Odontoscirus nipponicus Shiba, 1985 is recorded from China and is redescribed; male, tritonymph, deutonymph, protonymph, and larva are described and illustrated for the first time. Morphological observations on the ontogeny of this species are also provided.